Prevalence of physical activity using validated tools among adults during the COVID-19 pandemic in the Eastern Mediterranean region: A systematic review and meta-analysis. (September 2022) - Albelbeisi, Ahmed Hassan; Arab-Zozani, Morteza; Nemati, Marjan Khabiri; Shaqfa, Khalil Mostafa; Kakemam, Edris
Many interventions have been taken around the world to limit the spread of COVID-19. These interventions have affected people's lifestyles such as physical activity. The aim of this systematic review and meta-analysis was to determine the prevalence of physical activity using validated tools among adults during the COVID-19 pandemic in the Eastern Mediterranean region. A systematic literature review and meta-analysis were conducted in October 2021. We searched three electronic databases (Web of Science, Scopus, and PubMed) for English-language original articles of observational studies (cross-sectional, case–control, and cohort studies) with original data reporting the prevalence of physical activity among adults in 22 countries from EMR during the COVID-19 pandemic. Hoy's risk of Bias tool was applied to assess the biases in individual studies. The result was reported as a percentage for prevalence. A meta-analysis was conducted using the random-effect model with a 95% confidence interval. A total of 363 articles were retrieved. Finally, 15 articles were selected and included in the statistical analysis. The selected studies included 16, 585 participants. The result of the meta-analysis showed that the overall physical activity was 51.6% (95% confidence interval: 42.1, 61: p  = 0.745). The result of subgroup analysis based on different tools was 60.2%, 39.5%, 36.3%, 39.4%, and 55.2% for Global Physical Activity Questionnaire, The Godin-Shephard Leisure-Time Physical Activity Questionnaire, International Physical Activity Questionnaire, International Physical Activity Questionnaire–BREF, and International Physical Activity Questionnaire–short form, respectively. Our study highlights the urgent need for large-scale measurement and reporting of physical activity and the use of standard tools that can allow for the regular assessment and screening of the PA prevalence to support evidence-informed policy and programs development at both national and regional levels.